Satellite Remote Sensing Reveals Voluntary Cover-Crop Adoption and Crop-Rotation Hotspots in the Mississippi Alluvial Plain - Zobaer Ahmed; Lawson Connor; Kris Brye; V. Steven Green; Mike Popp; Aaron Shew; Lawton L. Nalley (PLoS ONE, 2025)
Government-subsidized programs like the Environmental Quality Incentives Program and the Conservation Stewardship Program provide financial motivation for adopting cover crops. Nevertheless, many producers have internalized the holistic benefits of cover crops and voluntarily adopted them as a sustainable soil management practice. Yet, little is known about how cover crop adoption propagates beyond the first order link between financial incentives and total adopted cover crop acres. This study examined voluntary adoption of winter cover crops as well as which crop rotations had the highest cover crop use in the Mississippi Alluvial Plain (MAP) region. Cover crop locations were identified using remote sensing technologies, ground-truthed government data sources, and the United States Department of Agriculture’s Cropland Data Layer. Results in this study revealed a 5.3% increase in total voluntary cover crop adoption in the study region from 2013 to 2019. The analysis also revealed four predominant cash crop rotations associated with the use of cover crops, with a soybean/soybean rotation having the greatest association with increased wintertime cover crop acreage. Results provided valuable insights for policymakers and stakeholders to promote sustainable agricultural practices, to foster further adoption of cover crops, and optimize cover crop integration into cropping systems in the MAP and other regions.